Hubungan Komunikasi Interpersonal Guru di Masa Pandemi dengan Minat Belajar Siswa - Reza Yuda Prawira; Ike Junita Triwardhani (UNISBA Press, 2023)
Abstract. The phenomenon of divorce in Indonesia is increasing and is even becoming a common thing. This of course is very bad for children. Children will be the victims who are most harmed. This phenomenon is commonly known as Broken Home, this term is often used nowadays to say how the atmosphere of the house is already